Study on the Mechanisms of Flavor Compound Changes During the Lactic Fermentation Process of Peach and Apricot Mixed Juice - Yao Zhao; Ruoqing Liu; Ying Mu; Mingshan Lv; Jun Xing; Li Zheng; Aihemaitijiang Aihaiti; Liang Wang (Foods)
This study employed headspace solid-phase microextraction gas chromatography–mass spectrometry (HS-SPME-GC-MS) and liquid chromatography–mass spectrometry (LC-MS) for non-targeted metabolomics analyses to examine the impact of mixed fermentation with various lactic acid bacteria (LAB) on the flavor compounds and metabolites of peach and apricot mixed juice (PAMJ), specifically focusing on the alterations of volatile compounds and non-volatile metabolites, as well as their metabolic pathways during the fermentation process. A total of 185 volatiles were identified using HS-SPME-GC-MS analysis, revealing significant differential metabolites, including eugenol, benzaldehyde, and γ-decalactone etc. The results indicated that lactic fermentation significantly enhanced the overall flavor of the juice toward the end of the fermentation process. In the interim, untargeted metabolomics utilizing LC-MS identified 1846 divergent metabolites, with 564 exhibiting up-regulation and 1282 demonstrating down-regulation. The metabolic pathway study performed by the Kyoto Encyclopedia of Genes and Genomes (KEGG) revealed significant changes in the metabolic levels of amino acids and saccharides after the lactic fermentation of PAMJ. Primarily associated with amino acid metabolism and starch and sucrose metabolism pathways. This work establishes a theoretical foundation for advancing fermented fruit juices with superior quality.